Hyper-reflective foci changes in RRMS under natalizumab therapy - Puthenparampil, Marco; Basili, Elisa; Ponzano, Marta; Mauceri, Valentina Annamaria; Miscioscia, Alessandro; Pilotto, Elisabetta; Perini, Paola; Rinaldi, Francesca; Bovis, Francesca; Gallo, Paolo (Frontiers in Immunology, 2024)
Since hyper-reflective foci (HRF) might mark MG activation, in vivo analysis by Optic Coherence Tomography (OCT) in MS patients under disease modifying therapies may help to clarify MS immunopathology as well as drug's mechanism of intrathecal action.Objective. To analyze HRF in patients treated with Natalizumab (NTZ), a high efficacy therapy for MS.The effect of NTZ on the retina of 36 Relapsing-Remitting MS patients was investigated in a prospective, single-centre study. OCT was performed immediately before the first infusion and then between infusion 3 and 4, infusion 6 and 7, infusion 11 and 13. Peripapillary and macular scans were acquired, evaluating peripapillary RNFL thickness, macular volumes (vertical scans), and HRF count (horizontal scan) in Ganglion Cell Layer (GCL), Inner Plexiform Layer (IPL) and Inner Nuclear Layer (INL).Clinical examination was performed every six months.Results. HRF count significantly increased under NTZ therapy (p<0.001) in both GCL (18.85±6.93 at baseline, 28.24±9.55 after 12 months) and IPL (25.73±7.03 at baseline, 33.21±8.50 after 12 months) but remained stable in INL (33.65±7.76 at baseline, 36.06±6.86 after 12 months, p=0.87), while no relevant modification of pRNFL and macular volumes were observed during the study. EDSS remained stable and no clinical relapse was observed between month 6 and 12.In RRMS NTZ affects HRF count in GCL and IPL, but not in INL, suggesting that NTZ does not impact on some aspects of MS immunopathology.